Aggregation induced emission: a land of opportunities. (3rd August 2017) - Liu, Bin; Pucci, Andrea; Baumgartner, Thomas
Abstract : Guest editors Bin Liu, Andrea Pucci and Thomas Baumgartner introduce this Materials Chemistry Frontiers themed collection on aggregation induced emission.